Penerapan Metode Tilawati dalam Meningkatkan Kefasihan dan Kelancaran Membaca Al-Qur'an Siswa Sekolah Dasar Islam Terpadu - Hafid Rifaat; Abdul Qodir; Zainap Hartati (SITTAH: Journal of Primary Education, 2025)
The student's ability to read the Al-Qur'an is still inadequate, so it was found that students were still not fluent in reading the Al-Qur'an. This study attempts to examine the use of the tilawati method in improving the fluency and smoothness of students reading the Al-Qur'an at SDIT Al-Qonita Palangka Raya. This study uses a quantitative research design with a descriptive quantitative approach, with data collection techniques through observation, interviews, and tests. The findings indicate that the tilawati method is effective in improving the ability to read the Al-Qur'an of students at SDIT Al-Qonita, especially in the aspects of tajwid and makhraj letters, where all students achieved perfect scores (average 35.00; standard deviation 0.000). However, in reading rhythm, variations in ability were still found (average 23.33 out of 30; standard deviation 4.082), indicating the need for further coaching. From the aspect of reading fluency, the average value of reading rules (44.00) and voice intonation (43.67) showed promising results, with an even distribution of values ​​(standard deviation around 4.3), so this method has been proven to provide a positive and consistent influence. However, improving the rhythm aspect needs to be a concern in the future.